STRATEGI PEMBELAJARAN PENDIDIKAN MENENGAH DI ERA DIGITAL - Bagas Permana Putra; Rizka Hayu Faradillah; Astriya Indah Sari; Rizka Elan Fadilah; I Ketut Mahardika; Firdha Yusmar (FKIP e-PROCEEDING, 2022)
Education is an effort that we do consciously to realize cultural heritage from one generation to another in the future. This education is realized by studying all the learning processes and seeing the learning atmosphere so that students can actively increase their potential to have intelligence, personality, religious spiritual strength, noble character, self-control and skills needed for themselves and others. Secondary education itself is a continuation of basic education which consists of junior secondary education and senior secondary education. In learning, secondary education in the digital era certainly requires strategies to facilitate students in the learning process. The learning strategy is a learning model that presents teaching materials covering all aspects before and after learning by educators as well as all facilities related to the teaching and learning process such as technology in the digital era. Education in the digital era must integrate all communication and information technologies into all student subjects to facilitate the teaching and learning process both offline and online. The purpose of writing this article is generally focused on how the strategy for implementing secondary education in the digital era is.